Postpartum Vaginal Blood Loss following Two Different Methods of Cervical Ripening - Okon Asuquo Okon; John Egede Ekabua (Hindawi Limited, 2017)
Eighty women undergoing induction of labor at the University of Calabar Teaching Hospital were recruited and randomly allocated into two treatment groups (40 each), to receive either serial 50 µg doses of misoprostol or intracervical Foley catheter. Vaginal blood loss was collected and measured using an under buttocks plastic collection bag and by perineal pad weighing up to 6 hours postpartum. There were no significant differences between the two groups with respect to sociodemographic and obstetric characteristics. Comparison of blood loss in vaginal deliveries between the two groups revealed that subjects in the misoprostol group had significantly higher blood loss than subjects in the Foley catheter group (488 ± 222 versus 326 ± 106, p<0.05). In both groups, there was strong and statistically significant positive correlation between postpartum blood loss and induction delivery interval (r=0.75, p<0.0001; r=0.77, p<0.0001). There were no significant differences in maternal outcomes. In view of this, further study is required to ascertain if lower doses of misoprostol for induction of labor may result in lesser blood loss. This trial is registered with ISRCTN14479515.